An empirical analysis : advertising effects on firm performance in the Malaysian consumer products sector - Gan,, Kien Siong (Universiti Malaysia Sarawak (UNIMAS), 2010)
The mam aim of this study was to determine whether there were significant relationship between advertising expenditure and firm performance among 46 consumer products firms listed on the main board of the Kuala Lumpur Stock Exchange (KLSE) from the period of 2004 to 2008. Advertising effects on firm performance is measured using two constructs which are firm profitability and firm value by adopting Ordinary Least Squares (OLS) regression analysis. The results of linear regression showed that there was a positive relationship between advertising variable and it is statistically significant with both variables of firm performance which are firm profitability and firm value whereas sales variable was found only to be significant with firm profitability but were found to be insignificant on firm value.